2021
DOI: 10.4103/ijoy.ijoy_78_20
|View full text |Cite
|
Sign up to set email alerts
|

Yoga as a Novel Adjuvant Therapy for Patients with Idiopathic Inflammatory Myopathies

Abstract: Context: Recent studies have demonstrated that physical activity is well tolerated by patients with idiopathic inflammatory myopathies (IIMs) and can have additional benefits as an adjuvant therapy to pharmacologic agents, especially if started early. To date, no studies have examined the effects of yoga on patients with IIMs. Aims: The aim of this study was to evaluate the effects of yoga on self-reported difficulty in performing activities of daily living (ADL) and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Indeed, infectious adverse events represent a common and fearsome complication of IIM-ILD, with a mortality rate of 41.2% (126). Nonpharmacological treatments, too, have a paramount role in IIM: low-load blood-flow restricted resistance training may reduce the rate of muscle loss in IBM (157), as well as constant training and physical activity in all patients affected by IIM, in whom aerobic and resistance exercises, as well as yoga (158), may be helpful in the overall management of the disease (159)(160)(161).…”
Section: Take-home Messagesmentioning
confidence: 99%
“…Indeed, infectious adverse events represent a common and fearsome complication of IIM-ILD, with a mortality rate of 41.2% (126). Nonpharmacological treatments, too, have a paramount role in IIM: low-load blood-flow restricted resistance training may reduce the rate of muscle loss in IBM (157), as well as constant training and physical activity in all patients affected by IIM, in whom aerobic and resistance exercises, as well as yoga (158), may be helpful in the overall management of the disease (159)(160)(161).…”
Section: Take-home Messagesmentioning
confidence: 99%
“…To date, only one article has been published looking at the effects and benefits of yoga in patients with myositis (Table 1 ). In this study published in February 2021, Kong et al examined the patients’ self-reported perception of difficulty in performing activities of daily living (ADLs), as well as muscle strength, both before and 8 weeks after weekly yoga intervention [ 25 ]. The measured outcomes were scores on a Myositis Activity Profile (MAP).…”
Section: Yoga and Musculaturementioning
confidence: 99%
“…The measured outcomes were scores on a Myositis Activity Profile (MAP). This is a measure of the Activities of Daily Living (ADLs) and Manual Muscle Testing (MMT) — measuring muscle strength in the axial, proximal and distal muscle groups [ 25 ]. The MAP score increased from 66.67 (SD: 25.34) before beginning yoga intervention to 69.17 (SD: 30.71) upon completion of the 8-week yoga program.…”
Section: Yoga and Musculaturementioning
confidence: 99%
See 2 more Smart Citations